“Implementación de un sistema para control de posicionamiento angular de 1 eje en una estación fotovoltaica de 1 kw” - Simbaña Caiza, Jhonatan Steven (2023)
The purpose of this project is to implement a system to control the angular positioning of an axis, which will allow increasing the use of solar irradiance in a 1 kW photovoltaic station, due to the fact that currently the waste of solar energy captured by photovoltaic systems fixed is poor. In the first place, the research was carried out in bibliographic sources, where the solar inclination angles, types of tracking systems and range algorithms were studied.